Self-Perception of Co-Assistant Students Regarding The Covid-19 Pandemic - Chairiza Muttaqien; Putri Chairani Eyanoer; Ririe Fachrina Malisie; Hemma Yulfi (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background: At the beginning of 2020, the world was shocked by a new type of coronavirus (SARS-CoV-2) whose disease was called Coronavirus disease 2019 (COVID-19). The research aims to determine the self-perception of Co-Assistant students regarding the COVID-19 pandemic. Method: The study was designed cross-sectional, which was conducted via sharing online links. Respondents must Co-Assistant students from a medical faculty in Indonesia and participated in the questionnaire filling between June 2020 and October 2020. This research is a descriptive study with a cross-sectional approach and conducted using primary data (online questionnaire Results: One hundred forty-nine students (149) of Co-Assistant students from several medical faculties all over Indonesia met the inclusive criteria. The samples were dominated by female respondents at 103 students (69.1%), while the male respondent accounted for only 46 students (30.9%). The first year of the Co-Assistant program with 94 respondents (63.1%) followed by the second year of the Co-Assistant program with 55 respondents (36.9%). The highest mean score in the fear zone came from the